Lendo Tolstói pelas lentes de Weber e Lukács: uma análise do romance Ressurreição - Maciel, Mateus Brandão (2019)
The aim of the paper is to analyse the novel Resurrection, written by Leo Tolstoy, establishing a dialogue with the sociology of Max Weber. It is possible to trace a connection between the author as of the differences and possibilities of approximation between sociology and literature. Both are ways of representing society, but literature is characterized by a work with form and science for its commitment to the explanation and understanding of empirical reality. Lukács's sociology of literature allows a regard to Tolstoy's literary work with the novel, relating its formal dimension to the social process. Resurrection and Tolstoy's oeuvre are closely related to the modernization process undergone by late nineteenth-century Russia, initiated by the abolition of servitude in the 1860s until the 1905 Revolution. Weber's explicit quotations of Tolstoy's work point to a particular reading of the author and allow a dialogue between them. Weber reads the tolstoyan novel from the perspective of the typical questions of his analysis, the tension between the ethics of responsibility and ultimate ends, the development of asceticism and fraternal love, and the “disenchantment of the world”. Resurrection rests on the radical opposition between nature and power. It is from this point of view that Tolstoy analyses the institutions of the Russian Empire, the bureaucracy, and the private ownership of the land, writing a narrative of redemption that meets its apex in the revelation of the Sermon on the Mount.